The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2188/jea.je20210385
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Mental Health of Mothers in Fukushima: Insights From the Fukushima Health Management Survey’s 8-year Trends

Abstract: With the aim of monitoring the mental and physical health of mothers and children following the Fukushima nuclear accident and providing them with necessary care, we have been conducting an annual survey of expectant and nursing mothers since 2011. The Pregnancy and Birth Survey is a mail-in survey of about 15,000 individuals, with a response rate of approximately 50.0% each year. In addition, because respondents to a survey conducted in the immediate aftermath of the disaster showed a particularly high rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The results of the survey from 2011 to 2018 showed that the prevalence of depressive symptoms among mothers was highest in the 2011 survey after the radiation accident and decreased over time. 12 The 4-year follow-up data from the survey showed that the prevalence of depressive symptoms was lower than the period immediately after the childbirth and decreased over time. 12 The proportion of mothers with radiation anxiety was higher in 2011 than in the 2014 follow-up survey, 12 suggesting lingering effects of the radiation accident, especially among mothers who gave birth immediately after the disaster.…”
Section: Outcomes and Follow-up: Summary Of The Results Of The Fhmsmentioning
confidence: 97%
See 4 more Smart Citations
“…The results of the survey from 2011 to 2018 showed that the prevalence of depressive symptoms among mothers was highest in the 2011 survey after the radiation accident and decreased over time. 12 The 4-year follow-up data from the survey showed that the prevalence of depressive symptoms was lower than the period immediately after the childbirth and decreased over time. 12 The proportion of mothers with radiation anxiety was higher in 2011 than in the 2014 follow-up survey, 12 suggesting lingering effects of the radiation accident, especially among mothers who gave birth immediately after the disaster.…”
Section: Outcomes and Follow-up: Summary Of The Results Of The Fhmsmentioning
confidence: 97%
“… 1 , 6 In brief, the FHMS consists of the Basic Survey 7 and four detailed surveys: the Thyroid Ultrasound Examination, 8 Comprehensive Health Check, 9 Mental Health and Lifestyle Survey, 10 and Pregnancy and Birth Survey (Figure 1 ). 11 , 12 The eligible population of the Basic Survey was mainly individuals registered as residents in Fukushima Prefecture between March 11 and July 1, 2011 (including evacuees) and residents of other prefectures who commute to Fukushima Prefecture, totaling approximately 2.05 million people. The eligible population for the detailed survey is shown in the methods section of each survey below.…”
Section: Main Features and Participants: Overview Of The Fhms Methodsmentioning
confidence: 99%
See 3 more Smart Citations